2007
DOI: 10.1002/ejic.200600986
|View full text |Cite
|
Sign up to set email alerts
|

Helical Transition‐Metal Complexes of Constrained 2,2′‐Bidipyrrins

Abstract: Nickel(II), palladium(II), zinc(II) and copper(II) complexes of new constrained 2,2Ј-bidipyrrin ligands (H 2 BDP) with a peripheral eight-membered ring were prepared and examined with respect to coordination modes and conformation. Ni II and Pd II ions form mononuclear complexes with a distorted square-planar N 4 coordination, which was determined for the palladium derivative by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 55 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…[26][27][28] A substitution of hydrogen atoms for any other group at these positions would directly enhance the intramolecular repulsion and, therefore, the lability in complexes of such tetrapyrroles. 2,2'-Bidipyrrin compounds have been explored before as nitrogen-containing ligands in a number of mono-and dinuclear transition-metal chelates, [17,20,22,24,25,29,30] and the propensity of the terminal positions for chemical transformations has occasionally been documented. [31][32][33][34] Stable iron chelates, such as 2, can indeed be obtained from these ligands (Scheme 1), and we report herein the preparation, structure, spectroscopic analysis, and biomimetic reactivity of a unique series of iron 2,2'-bidipyrrin complexes [FeX-A C H T U N G T R E N N U N G (bdp)] (X = F, Cl, Br, I).…”
Section: -A C H T U N G T R E N N U N G (Bdp)]mentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] A substitution of hydrogen atoms for any other group at these positions would directly enhance the intramolecular repulsion and, therefore, the lability in complexes of such tetrapyrroles. 2,2'-Bidipyrrin compounds have been explored before as nitrogen-containing ligands in a number of mono-and dinuclear transition-metal chelates, [17,20,22,24,25,29,30] and the propensity of the terminal positions for chemical transformations has occasionally been documented. [31][32][33][34] Stable iron chelates, such as 2, can indeed be obtained from these ligands (Scheme 1), and we report herein the preparation, structure, spectroscopic analysis, and biomimetic reactivity of a unique series of iron 2,2'-bidipyrrin complexes [FeX-A C H T U N G T R E N N U N G (bdp)] (X = F, Cl, Br, I).…”
Section: -A C H T U N G T R E N N U N G (Bdp)]mentioning
confidence: 99%
“…The situation is special for iron, as similar complexes of other 3d transition metals, such as Zn, Cu, Ni, Co, or Mn, are more readily available and relatively stable (though still reactive) in solution. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Abstract:…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the kind of oligopyrrolic ligand and the type of metal employed, metal helicates have been reported as single-helix, double-helix, and triple helix comformations. Bröring and co-workers reported the synthesis of a series of helically twisted metal complexes of constrained 2,2′-bidipyrrin ligands and showed that metal ions such as Ni­(II) and Pd­(II) forms a singly helix where as Zn­(II) forms a double helix. However, Cu­(II) ion was stabilized in both single-helix and double-helix structures.…”
Section: Introductionmentioning
confidence: 99%
“…As potential building subunits of helical assemblies, linear tetrapyrrole ligands, bidipyrrins, that is, directly linked dipyrrin dimers, [8,9] can be used to fabricate metal complexes, including [2 + 2]-type Zn II -assisted double helices [10] as well as roughly square-planar complexes formed with Ni II , Cu II , and Pd II[11] (Scheme 1). Because of the coordination properties of dipyrrins as monoanionic bidentate ligands, bidipyrrin-Zn II double helices are electronically neutral and therefore their enantiomers would be isolated from the racemic mixture by facile protocols such as chiral HPLC.…”
Section: Introductionmentioning
confidence: 99%